Exploring structure and role of engineering asset management system in production organisations. (2016) - El-Akruti, Khaled; Dwight, Richard; Zhang, Tieling
Little has been done in the literature on the structure of engineering asset management system (EAMS) and its relationship to production and organisational strategy. In this paper, the position of an EAMS within an organisational structure and its strategic role within a production organisation's strategy has been explored. It is argued that the structure and mechanism of EAMS play a key role in directing the production process and linking to the organisational strategy: the absence or inadequacies of asset-related activities cause insufficient production performance that negatively impacts on the strategic achievement. Production actions are mapped with reference to the activities of the hypothesised framework to stipulate the structure and role of engineering asset management system in a production organisation. Production organisations can use the developed framework to check the required adequacy of their activities of the EAMS for success.